Information systems strategic management : an integrated approach - Clarke, Steve , 1950- (Routledge Series in Information Systems, 2007)
This volume provides a guide to the strategic management of information systems within business and the public sector. It considers the need to manage information systems as a mixture of technical and social entities, within a broader context.